Sources of expertise in social enterprises - Allen, Robby A. (Wiley, 2020)
Social enterprises draw upon multifarious sources of expertise in pursuit of their social and business goals. The social enterprise's first source of expertise is that of their own relational experience derived from their previous employment or experiences and context expertise developed from a deep understanding of their own business. They seek advice from a wide expert‐support network favoring those associated with business acumen more than any other. The expert‐support network consists of eight distinct categories that are described in a comprehensive model.
Keywords: entrepreneurship; expert; networks; social enterprise